Male–female relationships in olive baboons (Papio anubis): Parenting or mating effort?. Issue 127 (February 2019) - Städele, Veronika; Roberts, Eila R.; Barrett, Brendan J.; Strum, Shirley C.; Vigilant, Linda; Silk, Joan B.
Abstract: Long-term male–female bonds and bi-parental investment in offspring are hallmarks of human society. A key question is how these traits evolved from the polygynandrously mating multimale multifemale society that likely characterized the Pan-Homo ancestor. In all three species of savanna baboons, lactating females form strong ties (sometimes called "friendships") with one or more adult males. For yellow baboons ( Papio cynocephalus ) and chacma baboons ( Papio ursinus ), several lines of evidence suggest that these relationships are a form of male parenting effort. In olive baboons ( Papio anubis ), females are thought to preferentially mate with their "friends", and male-female bonds may thus function as a form of mating effort. Here, we draw on behavioral and genetic data to evaluate the factors that shape male-female relationships in a well-studied population of olive baboons. We find support for the parenting effort hypothesis in that sires have stronger bonds with their infants' mothers than do other males. These bonds sometimes persist past weaning age and, in many cases, the sire of the previous infant is still a close partner of the female when she nurses her subsequent offspring. We find that males who have the strongest bonds with females that have resumed cycling, but are not currently sexually receptive, are more likely to sire the female's next offspring but the estimate is associated with large statistical uncertainty. We also find that in over one third of the cases, a female's successive infants were sired by the same male. Thus, in olive baboons, the development of stable breeding bonds and paternal investment seem to be grounded in the formation of close ties between males and anestrous females. However, other factors such as male dominance rank also influence paternity success and may preclude stability of these bonds to the extent found in human societies.